Association of peroxisome proliferator-activated receptor delta and additional gene-smoking interaction on cardiovascular disease - Yang, Wenqi; Mao, Shudan; Qu, Baoze; Zhang, Fengxiang; Xu, Zhaolong (Clinical and experimental hypertension (1993), 2017)
Aims: To investigate the impact of peroxisome proliferator-activator receptor delta (PPARD) gene polymorphism and additional gene-smoking interaction on cardiovascular disease (CVD) risk based on this Chinese population. Methods: A total of 1048 subjects (617 males, 431 females) with a mean age of 52.9 ± 14.1 years old were selected, including 520 CVD patients and 528 normal control subjects. The logistic regression model was used to examine the association between three SNPs and CVD risk, odds ratio (OR), and 95% confident interval (95%CI) were calculated. Generalized multifactor dimensionality reduction (GMDR) was employed to investigate the gene-smoking interaction. Results: Genotypes of variants in rs2016520 and rs9794 were associated with decreased CVD risk, and CVD risk was significantly lower in carriers of C allele of the rs2016520 polymorphism than those with the TT genotype (TC+CC versus TT), adjusted OR (95%CI) = 0.71 (0.56-0.86). In addition, we also found that CVD risk was also significantly lower in carriers of the G allele of the rs9794 polymorphism than those with the CC genotype (CG+ GG versus CC), adjusted OR (95%CI) = 0.69 (0.53-0.86). GMDR analysis suggested a potential gene-environment interaction between rs2016520 and smoking. Overall, the two-locus models had a cross-validation consistency of 10 of 10, and had the testing accuracy of 62.17%, and never smokers with TC or CC of the rs2016520 genotype have the lowest CVD risk, compared to smokers with TT of rs2016520, OR (95%CI) was 0.42 (0.23-0.66). Conclusions: The minor allele of rs2016520 and rs9794 in PPAR-δ and interaction between rs2016520 and non-smoking were associated with decreased risk of CVD.